Media Internet sebagai Sumber Belajar terhadap Minat Belajar Siswa - Putri Regina Gumalangit; Melizubaida Mahmud; Aqi Bahsoan; Sudirman Sudirman; Roy Hasiru (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This research aims to determine the effect of using internet media as a learning resource on students' learning interest in the Economics subject in Grade XI at SMA Negeri 1 Gorontalo. Thus research employs a survey method using questionnaires as the data collection instrument. The population consisted of Grade XI students, and a sample of 74 students was randomly selected using random sampling. Data were analyzed using descriptive statistics, prerequisite tests, classical assumption tests, and simple linear regression analysis. The results indicate a positive and significant effect of using internet media on students' learning interest in Economics for Grade XI students at SMA Negeri 1 Gorontalo. The findings are expressed in the linear equation Ý = 29.653 + 0.495X. The Y variable (Learning Interest) is valued at 29.653 when the X variable (Internet Media) is 0 or absent. For every 1% increase in the X variable (Internet Media), the Y variable (Learning Interest) increases by 0.495. The t-test analysis indicates a positive and significant effect of using internet media as a learning resource on students' learning interest, with a t-count of 9.588 > t-table value of 1,922 and a significance level of 0.000<0.05.